Upaya Peningkatkan Prestasi Belajar tentang Sistem Periodik Unsur melalui Metode KIMLA Pada Siswa Kelas X MIPA SMA - Setyawati, Happy (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. The national curriculum of learning takes place through the Scientific Approach, students are guided to be able to find learning material by themselves. Not all students can be easily active in learning, because they are afraid to ask questions, lazy even some do not understand so learning is increasingly confusing. Learning with the habits of students want to explain the teacher, making students less active in the learning process and the results obtained are not optimal. Chemistry is often considered to be an elusive lesson that causes studentdislike. Pleasant learning methods are needed so as to create joyful nuanced learning situations that make students absorbed, comfortable and excited. The learning method chosen in this study was the KIMLA learning method, namely the method of discussion using songs as a medium in learning Chemistry. With the KIMLA method, it is expected that there will be an increase in the activeness and learning achievement of students in the periodic Chemistry System Learning subject elements. This research is a Classroom Action Research conducted atSMA 1 Ceper Klaten, in the odd semester of the 2018/2019 academic year in September 2018 - October 2019, the target in this study was the tenth grade students of MIPA 1 with 28 students consisting of 12 sons and 16 daughters. Data obtained through observation are direct observations when taking student learning activities data, and assessment sheets are continued by analysis of the average pre-action test scores, cycle 1 and cycle II. The criteria for the success of giving an action are if students get a minimum score of 67 KKM, with the percentage of learning completeness 75% of 28 students, while the success criteria for learningactiveness are 80%. Based on the results of the research and discussion it was concluded that there was an increase in the activeness of students to 96.4% and 100% learning outcomes completed with an average of 79.